A 30 year old female with continuous dull pain following perforation during root canal treatment in lower left first molar tooth (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below:A 30 year old female reported to the Department of Conservative Dentistry and Endodontics with the complaint of continuous dull pain in her lower left first molar tooth. She told that the tooth was attempted for endodontic treatment three weeks before and the perforation might occur at that time. On clinical examination, although the tooth was found sealed coronally with a temporary cement but it was sensitive to percussion and palpation. The mean probing pocket depth was within the normal level of 2 mm. Radiographic examination revealed a destruction of pulpal floor area with radiolucency.